Internet censorship detected in Kazakhstan (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Kazakhstan. Data sourced from CensoredPlanet.
Censorship Incident ID: KZ-2026-0166. Severity: critical. Confidence: 65%